Trichoderma reesei Isolated From Austrian Soil With High Potential for Biotechnological Application - Hinterdobler, Wolfgang; Li, Guofen; Spiegel, Katharina; Basyouni-Khamis, Samira; Gorfer, Markus; Schmoll, Monika (Frontiers in Microbiology, 2021)
Fungi of the genus Trichoderma are of high importance for biotechnological applications, in biocontrol and for production of homologous and heterologous proteins. However, sexual crossing under laboratory conditions has so far only been achieved with the species Trichoderma reesei, which was so far only isolated from tropical regions. Our isolation efforts aimed at the collection of Trichoderma strains from Austrian soils surprisingly also yielded 12 strains of the species T. reesei, which was previously not known to occur in Europe. Their identity was confirmed with tef1- and rpb2-sequencing and phylogenetic analysis. They could clearly be distinguished from tropical strains including the common laboratory wildtypes by UP-PCR and genetic variations adjacent to the mating type locus. The strains readily mated with reference strains derived from CBS999.97. Secreted cellulase and xylanase levels of these isolates were up to 6-fold higher than those of QM6a indicating a high potential for strain improvement. The strains showed different responses to injury in terms of induction of sporulation, but a correlation to alterations in the nox1-gene sequence was not detected. Several synonymous SNPs were found in the sequence of the regulator gene noxR of the soil isolates compared to QM6a. Only in one strain, non-synonymous SNPs were found which impact a PEST sequence of NoxR, suggesting altered protein stability. The availability of sexually fertile strains from middle Europe naturally producing decent amounts of plant cell wall degrading enzymes opens up novel perspectives for non-GMO strain improvement and biological pretreatment of plant biomass for bioethanol production. Moreover, the varied response of these strains to injury in terms of sporulation, which is independent of Nox1 and NoxR suggests that additional regulators impact this phenomenon in T. reesei.